Desert networks: a conceptual model for the impact of scarce, variable and patchy resources - McAllister, R.; Holcombe, S.; Davies, J.; Cleary, J.; Boyle, A.; Tremblay, P.; Stafford Smith, D.; Rockstroh, D.; LaFlamme, M.; Young, M.; Rola-Rubzen, Maria Fay (Elsevier, 2011)
Social actors in arid regions must develop strategies to respond to available resources, which are scarce, variable, patchy and unpredictable relative to other regions. We explore our observations of relationships amongst people and organisations in Australian deserts using a stylised network model of the structure of social networks in arid systems. Results suggest that temporal resource variability drives increased network density, but with fewer strong ties; sparse populations drive a relatively higher proportion of strong ties, and that networks develop a hub configuration as resource endowments become more patchy spatially. These ideas highlight some issues that warrant improved understanding by actors seeking to enhance livelihoods and local resilience in these extreme environments.